Modeling thermal model of a disk coil with directed oil flow using matlab software - Ahmad, Nur Darina (2012)
Directed oil flow of a disk transformer in this model is guided by the oil flow washer. The model is established to investigate the temperature rise in the oil-filled transformer windings. Mass flow distribution and pressure drop concept are by using the number, size, location of horizontal ducts, fluid properties and the temperature variables. Pressure drop calculation is a temperature dependent and caused uniform heat distribution. An iterative solution is required to solve the equation to find the oil velocities, oil temperature and disk temperature. Because of the concept in every pass is the same, this model proposed to design in a single pass. The oil velocity and pressure at the last path can be used as input value to calculate the next pass. As disk temperature is very sensitive to the changes of the variables, so designing a suitable parameter for a single power transformer is very important. Matlab perform better in iterate equations and modeling disk transformer where the result is nearly accurate.